RISK FACTORS FOR DIARRHEA IN TODDLERS AGED 12-59 MONTHS AT THE CIKETING UDIK HEALTH CENTER, BEKASI CITY IN 2022 - Shafira Sulistiani; Munaya Fauziah; Andriyani; Nurmalia Lusida (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2024)
Dehydration is a common side effect of diarrhea, which can have major repercussions if left untreated. When it comes to nutrition and health, toddlers are a particularly sensitive age group. Diarrhea is common in the residential area next to the landfill because of contaminated water sources and inadequate sanitation. This study used a cross-sectional, quantitative research methodology to identify the risk factors for diarrhea in children aged 12 to 59 months at the Ciketing Udik Health Center in Bekasi City in 2022. moms of toddlers in Pomegranate Posyandu 1–5 at the Ciketing Udik Health Center in Bekasi City comprised the study's population, and there were 98 moms in all. This was obtained by the use of stratified sampling. The findings demonstrated that maternal knowledge P-value (0.001), hand washing behavior P-value (0.013), mother's habit of purchasing food outside P-value (0.046), and compliance with zinc tablet administration P-value (0.016) were the factors most significantly linked to the incidence of diarrhea in toddlers aged 1–5 years at Puskesmas Ciketing Udik Bekasi City. These findings suggest that the occurrence of diarrhea in toddlers is correlated with maternal education, hand-washing practices, eating-out behaviors, and adherence to zinc tablet delivery. In order to prevent diarrhea, moms of young children might take precautions as soon as feasible.